EFEKTIVITAS BADAN PERMUSYAWARATAN DESA DALAM PENGAWASAN KINERJA KEPALA DESA PANCIRO KECAMATAN BAJENG KABUTAEN GOWA PERSPEKTIF SIYASAH SYARÍYAH - Soleh, Muhammad Ikhsan; Hasan, Hamzah; Fatmawati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
Good governance can be seen from aspects, oneofthem is measuring the maturity of government institutions in carriying out their functions and rules, from the lowest level to the highest in the government sysrem. Indonesia is known as a coutry that implments a decentralized system, which makes local governments run their own government, in the case at the village government level also gets is own authority in regulating its government, therefore, to provide a balance in running the govermentin the village, the village head neads partners in running the government, so a legislative body is formed, known as the village consultative body (BPD), one of the duties and functions of the BPD is to provide supervision over the performance of the village head in carrying out his duties as head of government at the village level. Departing from this background, the author takes two main problems, namely the from of BPD panciro’s supervision of the village head, and the view of Islamic law on the supervisory function carried out by the BPD against the village head. In this study the author uses a qualitative field research method. As for the research result obtained from the research location, firstly, the panciro’s BPD in carrying out its supervisior function is carried out in a complrkx and family manner, for example in a work program, the BPD involves itself starting from program planning, to the realization stage, so that it can provide supervision as well as performance appraisel fillage head. Secondly, in Islamic low or in this case siyasah syaríah known al-Hisbah which means calling for good and keeping away from evil, seeing the from of supervision carried out by the panciro BPD, then this concept is indirectly developing in government where the BPD as much as possible prevents irregularities deviations that can harm society.